Modelling, Simulation and Social Network Data: What’s New for Public Health and Epidemiology Informatics? - Toubiana, L.; Griffon, N; Section Editors for the IMIA Yearbook Section on Public Health and Epidemiology Informatics (Yearbook of Medical Informatics, 2015)
Objectives: Summarize excellent current research in the field of Public Health and Epidemiology Informatics.Method: Synopsis of the articles selected for the IMIA Yearbook 2015.Results: Four papers from international peer-reviewed journals have been selected as best papers for the section on Public Health and Epidemiology Informatics.Conclusions: The selected articles illustrate current research regarding the impact and assessment of health IT and the latest developments in health information exchange.
Keywords: Public health; epidemiology; medical informatics; International Medical Informatics Association; health information systems; hospital information systems